2021
DOI: 10.3390/cli9100146
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Climate Action in Canada’s Provincial North? Exploring the Role of Connectedness to Nature, Climate Worry, and Talking with Friends and Family

Abstract: Despite widespread calls to action from the scientific community and beyond, a concerning climate action gap exists. This paper aims to enhance our understanding of the role of connectedness to nature in promoting individual-level climate action in a unique setting where climate research and action are lacking: Canada’s Provincial North. To begin to understand possible pathways, we also examined whether climate worry and talking about climate change with family and friends mediate the relationship between conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 92 publications
1
15
0
Order By: Relevance
“…Regarding predictors of private-sphere pro-environmental behaviour among young people, climate-change worry is one factor that is consistently positively related to being more engaged (Galway et al, 2021; for a review, see Ojala et al, 2021;Sanson et al, 2019). One mediating factor in this relationship is problem-focused coping, where people cope by focusing on the problem and searching for information (Ojala, 2012b).…”
Section: Positive Youth Development: Private Sphere Climate-change En...mentioning
confidence: 99%
“…Regarding predictors of private-sphere pro-environmental behaviour among young people, climate-change worry is one factor that is consistently positively related to being more engaged (Galway et al, 2021; for a review, see Ojala et al, 2021;Sanson et al, 2019). One mediating factor in this relationship is problem-focused coping, where people cope by focusing on the problem and searching for information (Ojala, 2012b).…”
Section: Positive Youth Development: Private Sphere Climate-change En...mentioning
confidence: 99%
“…This divergence from existing scholarship on climate emotions could be due, in part, to the fact that our sample only included adults aged 18 and up; therefore, the experiences of youth and children are not captured in our data. This divergence could also be explained, in part, by the strong connectedness to land and nature that is common and characterizes the Provincial North (Galway et al, 2021), which likely enhances experiences of emotional distress in relation to climate change and increases with age and living in a particular community for a long period (which is the case for our sample). However, our results regarding age are in line with Wullenkord et al (2021) who found no bivariate correlation between age and climate anxiety specifically.…”
Section: Discussionmentioning
confidence: 93%
“…The postal surveys were implemented in two communities within the regional case-study setting: Thunder Bay (Northern Ontario) and Prince George (Northern British Columbia). See Galway et al (2021) for a more complete description of these two communities. This paper uses the data collected via these postal surveys to explore and enhance understanding of climate emotions in the context of Canada's Provincial North.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may also influence perception of already existing degradation of nature due to climate change, which may exacerbate feelings of climate anxiety. These conceptual thoughts are mirrored in tentative evidence for a positive relationship of nature connectedness with climate worry (17,18) and climate anxiety (12). The existing studies operationalized nature connectedness as a partially cognitive construct, rather than as the affective construct that Mayer and Frantz propose.…”
Section: Predicting Climate Anxietymentioning
confidence: 95%